Religious Moderation in the Digital Era: Strengthening Social Tolerance amid Digital Diversity - Ameliana Nurahmi; Zulvia Rahmi; Rohadatul Aisi; Iswantir M; Yulia Rahman (STIT Ahlussunnah Bukittinggi, 2026)
Religious moderation has become increasingly important in addressing the challenges of contemporary social life shaped by digital technology, rapid information exchange, and intensified intercultural and interreligious interactions. This study examines the role of religious moderation in fostering tolerance amid digital diversity and explores the challenges posed by the spread of intolerant, provocative, and radical content on digital platforms. Employing a qualitative library research design with a content analysis approach, data were collected from scholarly journals, books, policy documents, and other relevant literature on religious moderation and digital social dynamics. The findings indicate that religious moderation contributes significantly to promoting social harmony through the reinforcement of tolerance, interfaith dialogue, inclusivity, and responsible digital literacy. The study also reveals that hate speech, social polarization, misinformation, and the misuse of social media constitute major obstacles to the development of tolerant digital communities. Furthermore, effective implementation of religious moderation requires collaborative efforts among educational institutions, governments, religious leaders, and civil society organizations. The study concludes that religious moderation serves as a critical framework for strengthening social cohesion, preserving national unity, and fostering peaceful coexistence within increasingly diverse digital societies.